2019
DOI: 10.1186/s13244-019-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment of hepatocellular carcinoma after locoregional therapy

Abstract: Liver cirrhosis and hepatocellular carcinoma (HCC) constitute one of the major causes of morbidity, mortality, and high health care costs worldwide. Multiple treatment options are available for HCC depending on the clinical status of the patient, size and location of the tumor, and available techniques and expertise. Locoregional treatment options are multiple. The most challenging part is how to assess the treatment response by different imaging modalities, but our scope will be assessing the response to loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 110 publications
1
21
0
Order By: Relevance
“…‘Nodule-in-nodule’ enhancement should be interpreted as an epithelioid angiomyolipoma, and the lack of blood supply or ring enhancement should be interpreted as isolated necrotic nodules and metastasis. 13 This was a retrospective study based on conventional MRI and was limited to the pathological group with possible overlapping signs. Additionally, specific examination sequence support for prediction of the texture type was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…‘Nodule-in-nodule’ enhancement should be interpreted as an epithelioid angiomyolipoma, and the lack of blood supply or ring enhancement should be interpreted as isolated necrotic nodules and metastasis. 13 This was a retrospective study based on conventional MRI and was limited to the pathological group with possible overlapping signs. Additionally, specific examination sequence support for prediction of the texture type was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the obvious contrast resolution of MRI especially with subtracted images helps in discriminating post-therapy changes from residual or recurrent tumor as well as detecting newly developed lesions. Moreover, MRI is superior to CT in the surveillance for patients after treatment to minimize radiation exposures and hazards of contrast agents especially if young-aged [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the improvement in diagnostic accuracy of CEUS in the detection and characterization of FLLs, including HCC [8][9][10][11]. CEUS has been also proved useful in the guidance and response assessment of therapeutic procedures [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%